PENGEMASAN BUAH DAN SAYUR DENGAN ATMOSFIR TERMODIFIKASI - Pardede, Erika (LPPM Universitas HKBP Nommensen, 2020)
Being living organs, fresh harvested fruits and vegetables remain metabolically active and undergo ripening and senescence processes. They needs oxygen to stay alive, which is vital for energy production through respiration process. Modified Atmosphere Packaging (MAP) technology utilises in-packaging equilibrium atmosphere, in which the relatively low oxygen and high carbondioxide concentration is achieved naturally inside the package as respiration occurs, which later on leads to a lower respiration rate. Low oxygen concentration could also be achieved by replacing some oxygen with nitrogen and/or application of oxygen scavenger inside in package, thus the respiration rate is reduced and the aging process is retarded. The use of packaging films of correct intermediary permiability to meet a desirable equilibrium modified atmosphere become a key to the succes of MAP. A new technique, so called Perforation-Mediated Modified Atmosphere Packaging (PM-MAP), by having microperforation in the plastic films is applied to correct the exchange of air during storage. Therefore Modified Atmosphere Packaging (MAP) technology offers advantages which leads to extension of the shelf life of fresh produces. Fresh and fresh-cut food industry utilise this advantages to meet the growing demand of convinient and fresh quality fruits and vegetables, in order to maintain freshness quality attributes and to extend the shelf life.